Estimation of Excess Deaths Associated With the COVID-19 Pandemic in Istanbul, Turkey - Ucar, Abdullah; Arslan, Seyma (Frontiers in Public Health, 2022)
Background & objectives: The official number of daily cases and deaths are the most prominent indicators used to plan actions against the COVID19 pandemic but are insufficient to see the real impact. Official numbers vary due to testing policy, reporting methods, etc. Therefore, critical interventions are likely to lose their effectiveness and better-standardized indicators like excess deaths/mortality are needed. In this study, excess deaths in Istanbul were examined and a web-based monitor was developed. Methods: Daily all-cause deaths data between January 1, 2015- November 11, 2021 in Istanbul is used to estimate the excess deaths. Compared to the pre-pandemic period, the % increase in the number of deaths was calculated as the ratio of excess deaths to expected deaths (P-Scores). The ratio of excess deaths to official figures (T) was also examined. Results: The total number of official and excess deaths in Istanbul are 24.218 and 37.514, respectively. The ratio of excess deaths to official deaths is 1,55. During the first three death waves, maximum P-Scores were 71,8%, 129,0%, and 116,3% respectively. Conclusion: Excess mortality in Istanbul is close to the peak scores in Europe. 38,47% of total excess deaths could be considered as underreported or indirect deaths. To re-optimize the non-pharmaceutical interventions there is a need to monitor the real impact beyond the official figures. In this study, such a monitoring tool was created for Istanbul. The excess deaths are more reliable than official figures and it can be used as a gold standard to estimate the impact more precisely.